PLASMA CALCIUM, PHOSPHORUS AND MAGNESIUM PROFILE IN POSTPARTUM COWS FOLLOWING HORMONAL THERAPY - PATEL, P M; DHAMI, A J; KAVANI, F S (The Indian Journal of Animal Reproduction, 2011)
Recently calved HF cows (24) ofUniversity farm were monitored for weekly plasma profile of calcium, phosphorusand magnesium from the day of calving till 21 st week postpartum following GnRH (Receptal) and PGF 2 alpha(Lutalyse) treatment at 7th week in anestrus and subestrus cows (6 each, keeping equal number as control),respectively. The plasma calcium levels in subestrus cows were significantly higher as compared to anestruscows at 7th, 8th, 17th and 21 s1 week postpartum, including overall mean (8.17±0.08 vs 7.72±0.08 mg/di), whilephosphorus levels were lower throughout the postpartum period, but varied significantly at calving and then at 1st-3rd and 13th week postpartum (overall mean 6.96±0.07 vs 7.12±0.06 mg/di). The calcium and phosphorus levelswere low at calving in all the groups, and increased linearly and significantly throughout the postpartum period insubestrus cows. Further, the cows of GnRH treatment group, in comparison to control, had significantly lowercalcium levels at 1 s1, 5th, 8th and 19th weeks postpartum, butthis trend was inversed between PGF 2a treatment andcontrol groups. The mean plasma Ca:P ratio was higher throughout the postpartum period in subestrus cows a~compared to anestrus cows, and it differed significantly at 13th, 17th- 18th and 21st week postpartum. The magnesiumlevels of anestrus and subestrus cows (2.95±0.04 vs 3.14±0.01 mEq/L) did not differ significant at any of theintervals postpartum. Throughout the postpartum period magnesium levels were lower in GnRH treatment than thecontrol group, but varied significantly only at 5th-10th and 13th- 15th week postpartum, whereas it was higher in PGF 2aipha treatment than the control group, and differed significantly from calving to 4th week.and again from 14th-20th weekpostpartum. The trend of plasma calcium, phosphorus levels reflected physiological/homeostatic mechanism ofmineral metabolism and the hormone GnRH or PGF 2a treatment did not influence it.
Keywords: GnRH; PGF2alpha; Calcium; Phosphorus; Magnesium; Postpartum cows